Application of vegetable oils as pharmaceutical ingredient: the impact of liquid lipid type on the characteristics of nanostructured lipid carrier - Binarjo, Annas; Ernidawati; Khotimah, Khusnul; Wahyuningsih, Iis; Efiana, Nuri Ari (Pharmaciana, 2024)
Recently, drug encapsulation using a Nanostructured Lipid Carrier (NLC) has gained attention in formulation studies due to its high loading capacity and prevent drug expulsion during storage. Drug loading capacity is mainly affected by lipid type and composition, especially liquid lipids. Therefore, this research aims to evaluate the potential of avocado oil as a liquid lipid of NLC replacing pure oleic acid. All components including oil, glyceryl monostearate, Tween 20®, and Span 60® were processed to NLC by solvent injection method. The colloidal characteristics of NLC dispersion in water and 20 mM PBS pH 7 were determined, including transmittance, particle size, size distribution, zeta potential, loading capacity (LC), and loading efficiency (LE) of capsanthin in NLC. The results showed that NLC containing oleic acid (Fola) and avocado oil (Favo) dispersion in PBS exhibited a similar transmittance and zeta potential of 69-74% and -51 to -58 mV, respectively, whereas the particle size and size distribution of Favo were significantly higher than Fola. Moreover, the 1.3-fold higher LC and LE of Favo compared to Fola was insignificant (p>0.05).   Additionally, the Tween 20® and Span 60® ratio of Favo should be improved to obtain an ideal particle size and size distribution as in Fola.  In conclusion, avocado oil indicated the potential to be utilized as a liquid lipid of NLC formulation regarding zeta potential and drug loading. However, the surfactant composition should be adjusted to reduce the particle size of the NLC, leading to permeability enhancement in delivery, particularly oral administration.